Konsultasi Hukum Jual Beli Tanah sebagai Wujud Pengabdian Masyarakat: Studi Pengalaman Magang di Kantor Notaris Tjoeng Indryani Kusuma Lestari, SH - Alfarizi, Muhammad Salman (Community : Jurnal Pengabdian Pada Masyarakat, 2025)
Legal consultation provided by notary offices serves not only a practical role in assisting the public with legal issues, but also carries educational and preventive dimensions to reduce future legal disputes. This article is based on the author's internship experience at the Notary Office of Tjoeng Indryani Kusuma Lestari, SH, located in Sukabumi City. During the internship, the author was directly involved in assisting the office staff in providing legal consultations to the public, particularly in matters related to land sale and purchase. Using a descriptive-qualitative approach, this article examines how such consultations can be considered a form of community service, especially in fostering legal awareness and minimizing the risk of illegal transactions. The findings show that most members of the community do not fully understand the legal procedures involved in land transactions and often hold misconceptions about practical implementation. Therefore, the role of the notary as a legal information provider is crucial in creating safe, valid, and just transactions.